(untitled) - Somit, Albert (New York, 2003)
The essays in this collection explore the implications that the growing challenge from "evolutionary" concepts of human nature have in various policyareas and show what must be done to ensure that policies conform to humanbehavior and its limits for change. As our conceptualizations of humanbehavior switch from one that says human behavior is a product of culture(through learning and socialization) to one that claims that behavior isthe outcome of both cultyre and genetics and biology, it is necessary for public policy to change as well. The contributors in this volume examine what happens when it is no longer possible to base policy solely on the basis ofculturally-constructed human behavior. Many argue that to ignore "nature" onbehalf of "nurture" will result in incomplete solutions to social, political, and economic problems.
Keywords: Policy sciences,Human behavior